Plant innate immunity against human bacterial pathogens - Melotto, Maeli; Panchal, Shweta; Roy, Debanjana (Frontiers in Microbiology, 2014)
Certain human bacterial pathogens such as the enterohemorrhagic Escherichia coli and Salmonella enterica are not proven to be plant pathogens yet. Nonetheless, under certain conditions they can survive on, penetrate into, and colonize internal plant tissues causing serious food borne disease outbreaks. In this review, we highlight current understanding on the molecular mechanisms of plant responses against human bacterial pathogens and discuss salient common and contrasting themes of plant interactions with phytopathogens or human pathogens.